Development of a motorized food stirrer for use of cooking / Muhammad Irfan Syamil Firdaus - Firdaus, Muhammad Irfan Syamil (2024)
Cooking can be a very exhaustive process especially if the stirring aspect in cooking. This could burden old people, disabled people and small businesses that wants to cook their food easily. Therefore, this project can help mitigate those problems and makes cooking a hassle-free process in the stirring sides of the process. This is because, this machine that called motorized food stirrer, uses it motor to stir making it a hands-free process and it can even be automated while people focus on other aspect. The problem statement for this project is that exhaustive process as cookers need to focus on stirring their food carefully and it very tiresome for small businesses that wants to make large batches of food. It also costly for small businesses, they need to hire cookers and assistance to help them make food as they could not focus on one aspect. By designing and fabricating this project, it can help mitigate these problems and helpful for small businesses. This project is design by comparing to other existence product in the market. This could help in shaping the design for this project and have some benchmarking when designing this project. Next, is trying to relate some manufacturing process in the design which is cutting, joining, and finishing. After that, is to find the sustainability for this project by looking at the performance, economy, target production cost, size and weight, appearance, safety, precaution, ergonomics.